Resident alien omnibus, volume 2 ebook - Hogan, Peter (Resident Alien, 2023)
The series that inspired the SYFY original television series, starring Alan Tudyk!A stranded alien explorer—hiding in plain sight—has been posing as a doctor and solving crimes in the small town of Patience, Washington. After Harry accidentally exposes himself to investigators who are on his trail, a mysterious arsonist and a stubborn federal agent arrive in town to heat things up!The local sheriff must decide if he'll remain loyal to his inquisitive friend Harry, and nurse Asta finally realizes the danger she and Harry are both in. Peter Hogan (2000 AD, Tom Strong) and Steve Parkhouse (War Birds, Milkman Murders) continue their unique, acclaimed science-fiction/murder-mystery series!This omnibus collects the Resident Alien graphic novels Volumes 4 to 6, The Man with No Name, An Alien in New York, and Your Ride's Here, along with the Free Comic Book Day 2022 short story "The Ghost."